Long-term preservation of Lotus tenuis adventitious buds - Espasandin, Fabiana Daniela; Brugnoli, Elsa Andrea; Ayala, Paula G.; Ayala, Lilian P.; Ruiz, Oscar Adolfo; Sansberro, Pedro Alfonso (Springer, 2018)
Encapsulation-dehydration, encapsulation-vitrification, and vitrification were tested for cryopreservation of Lotus tenuis (Fagaceae) adventitious buds clusters (ABCs) obtained by a direct regeneration system from leaves cultures. Among them, the PVS3-based vitrification procedure was found to be useful for survival and regrowth of the preserved explants. For vitrification, the ABCs were dehydrated in a solution containing 2 M glycerol + 0.4 M sucrose for 25 min at room temperature, submerged in PVS3 solution for 1 h at 0 °C, then immersed in liquid nitrogen for 48 h and rapidly rewarmed. Afterword, the explants were unloaded in MS liquid medium with 1.2 M sucrose for 30 min. The washed tissues were dried superficially on filter paper and cultured in semisolid hormone-free MS medium containing 0.1 M sucrose. All cultures were maintained at 25 °C in the dark for 10 days and transferred to the light conditions. With this procedure, 79 ± 5.3% survival and more than 80% of the plantlets displaying a phenotype similar to the non-treated control after acclimatization. The data settled from ISSR showed no genetic dissimilarities between in vitro regenerants derived from cryopreserved tissues and the non-treated plants. Thus, our results indicate that the use of vitrification-based PVS3 solution offers a simple, accurate, and appropriate procedure for the cryopreservation of L. tenuis adventitious buds.